2014
DOI: 10.1182/blood-2014-01-453167
|View full text |Cite
|
Sign up to set email alerts
|

Erythro-megakaryocytic transcription factors associated with hereditary anemia

Abstract: Most heritable anemias are caused by mutations in genes encoding globins, red blood cell (RBC) membrane proteins, or enzymes in the glycolytic and hexose monophosphate shunt pathways. A less common class of genetic anemia is caused by mutations that alter the functions of erythroid transcription factors (TFs). Many TF mutations associated with heritable anemia cause truncations or amino acid substitutions, resulting in the production of functionally altered proteins. Characterization of these mutant proteins h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 109 publications
2
39
0
Order By: Relevance
“…The absence of apparent defects in granulocyte and monocyte lineage cell number (data not shown) suggests that Pcbp2 loss has a greater impact upon the megakaryocyte-erythrocyte progenitor (MEP) cell population. Several transcription factors regulate MEP lineage determination (KLF1 and FLI1) and maturation of erythrocytes and megakaryocytes (GATA1, TAL1, FOG1, NF-E2, and GFIIB) (86). We observed downregulation of Klf1, Tal1, and Nfe2 in Pcbp2 Ϫ/Ϫ 12.5-dpc fetal liver, which decreased 42%, 46%, and 60%, respectively ( Fig.…”
Section: Fig 7 Transcriptome Analysis Of Pcbp2mentioning
confidence: 70%
“…The absence of apparent defects in granulocyte and monocyte lineage cell number (data not shown) suggests that Pcbp2 loss has a greater impact upon the megakaryocyte-erythrocyte progenitor (MEP) cell population. Several transcription factors regulate MEP lineage determination (KLF1 and FLI1) and maturation of erythrocytes and megakaryocytes (GATA1, TAL1, FOG1, NF-E2, and GFIIB) (86). We observed downregulation of Klf1, Tal1, and Nfe2 in Pcbp2 Ϫ/Ϫ 12.5-dpc fetal liver, which decreased 42%, 46%, and 60%, respectively ( Fig.…”
Section: Fig 7 Transcriptome Analysis Of Pcbp2mentioning
confidence: 70%
“…In particular, we plan to include a larger number of red cell enzyme genes and add red cell membrane genes to the panel. Furthermore, the diagnostic utility of such panels depends on a regular process of review to accommodate relevant newly identified pathogenic and modifying mutations in genes and their promoters and regulatory elements (Crispino & Weiss, 2014). It is likely that whole exome sequencing or whole genome sequencing, which provide a much more comprehensive, unbiased approach, will replace targeted sequencing in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Germ line mutations of GATA1, which resides on the X chromosome, cause a variety of sex-linked recessive forms of hereditary thrombocytopenia and dyserythropoietic anemia. 3 Furthermore, acquired somatic mutations in GATA1 accompany the development of Down syndrome (DS) transient abnormal myelopoiesis, hereafter referred to as transient myeloproliferative disorder (TMD), and myeloid leukemia associated with DS, hereafter referred to as DS acute megakaryoblastic leukemia (DS-AMKL). 4,5 Germ line GATA2 mutations are responsible for GATA2 deficiency syndrome.…”
mentioning
confidence: 99%